2012
DOI: 10.1002/masy.201251118
|View full text |Cite
|
Sign up to set email alerts
|

Novel Microorganisms Resistant HDPE Composites with Wood Fiber and Nanosilica Containing Immobilized Nanosilver

Abstract: Summary: The effect of silica containing immobilized nanosilver (SiO 2 À Ag) on the structure, mechanical and bactericidal properties of wood-filled high density polyethylene composites compounded in a co-rotating twin-screw extruder and then injection molded was investigated. Maleated high density polyethylene (MHDPE) was used to improve mechanical properties, while spherical nanosilica containing immobilized nanosilver modified bactericidal properties of wood-filled HDPE composites. It was found that the add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…In addition, Yeo et al found that the AgNPs could act as impurities in the polymer matrix and interfere with the crystallization process of LDPE, causing the lower crystallinity. This phenomenon is very consistent with the previous studies in the literature where the AgNP content was varied in other types of polyethylene . The addition of AgNPs has no effect on the melting point ( T m ) of LDPE, ranging from 105.95 to 106.61°C.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, Yeo et al found that the AgNPs could act as impurities in the polymer matrix and interfere with the crystallization process of LDPE, causing the lower crystallinity. This phenomenon is very consistent with the previous studies in the literature where the AgNP content was varied in other types of polyethylene . The addition of AgNPs has no effect on the melting point ( T m ) of LDPE, ranging from 105.95 to 106.61°C.…”
Section: Resultssupporting
confidence: 92%
“…The extent of load transfer depends on the specific surface area and adhesion strength at the interface of the filler . Jeziorska et al suggested that although the crystallinity of polyethylene is reduced by incorporating nanofillers, an improvement in the tensile modulus can be observed because of the contribution of filler rigidity and good interfacial adhesion between the polymer matrix and the nanofiller.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, they showed that the presence of nanoparticle agglomerations might mask the effects of the higher crystallinity on melting temperature. [ 43 ] According to obtained results, it could be concluded that the melt temperature (T m ) was generally increased at higher ZnO ratios; however, HDPE melting temperatures were not substantially influenced by adding ZnO nanoparticles.…”
Section: Resultsmentioning
confidence: 83%
“…It is well known that PE mechanical properties can be enhanced by the addition of a small amount of reinforcing agents such as inorganic nanoparticles . Many studies focused on differently shaped fillers (lamellar, acicular, spherical) such as clay, titania, and silica in order to improve the mechanical properties of PE.…”
Section: Introductionmentioning
confidence: 99%